Effect of cultivation and timing of nitrogen fertilization on large patch disease of zoysiagrass - Obasa, Ken C.; Fry, Jack D.; St. John, Rodney A.; Kennelly, Megan M. (My University, 2013)
Large patch of zoysiagrass (Zoysia spp.) is caused by Rhizoctonia solani anastomosis group 2-2 LP. The effects of summer cultivation (core-aerification, verticutting, and sand topdressing) and spring and fall versus summer nitrogen (N) fertilization on large patch in fairway height ‘Meyer’ zoysiagrass were investigated from 2008 to 2011 in Manhattan, Haysville, and Olathe, KS. Disease was assessed by measuring patch diameters or analyzing digital images of affected plot areas to determine the percentage of non-green turfgrass within patches. Cultivation did not affect thatch temperature, soil temperature, soil water content, or turf recovery from large patch in early summer. Furthermore, cultivation did not result in overall significant reductions in patch diameters or average weekly rate of patch diameter increase among plots at the three experimental locations. In some site–year combinations, spring and fall N fertility was associated with lower percentages of non-green turf within affected plot areas in Manhattan and Haysville. In some cases, applications of N during spring and fall may alleviate large patch symptoms.
Citation: Obasa, K., . . . & Kennelly, M. (2013). Effect of Cultivation and Timing of Nitrogen Fertilization on Large Patch Disease of Zoysiagrass. Plant Disease, 97(8), 1075-1081. https://doi.org/10.1094/PDIS-10-12-0942-RE
Keywords: Zoysiagrass; Large patch disease; Nitrogen fertilization; Rhizoctonia solani